Mapping Research on Entrepreneurship and Tourism in Indonesia: A Bibliometric Analysis - Pahrudin Pahrudin; Muhamad Ali (UIN Fatmawati Sukarno Bengkulu, 2024)
Entrepreneurship and tourism have gained attention from researchers due to their contribution to society's social and economic welfare, especially in Indonesia. This study aims to analyze scientific literature on entrepreneurship and tourism in Indonesia by using the Scopus database. Bibliometric analysis was performed to analyze the documents to answer the research questions. A sample of 48 documents is selected and analyzed using R software (Biblioshiny). The result finds that entrepreneurship and tourism in Indonesia, widely studied by Indonesia University as an affiliated, contributed most to the documents. The thematic areas of entrepreneurship and tourism in Indonesia are entrepreneurship, tourism, innovation, rural tourism, sustainable tourism, and training. The entrepreneurship and tourism sector supports economic and sustainable development to support ecotourism based on the natural or to reach sustainable tourism. This study contributes to practical and theoretical studies of entrepreneurship and the tourism sector in Indonesia.